Perancangan Antena Dengan 2 Slot C Patch Lingkaran Planar Array 8 Elemen Dengan Defected Ground Structure Untuk Jaringan Komunikasi LTE 1800 MHZ - Jherino Permana Putra; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
In this paper, a microstrip antenna with eight-elements planar array by using Defected Ground Structure technique is designed for LTE application. The proposed antenna operates at 1800 MHz. The substrate FR-4 with dielectric constant of 4,3 and thickness of 1,6 mm is chosen. The antenna is simulated in CST microwave studio. From the simulation results, the return loss of -32,628 dB at 1800 MHz is obtained with 400 MHz of bandwidth. The VSWR ≤ 1,0479 and gain of 13,8 dBi are also presented.Keywords: DGS, Return loss, Bandwidth, VSWR, Gain